Effect of hydrogen on the ideal shear strength in metals and its implications on plasticity: A first-principles study. (21st July 2021) - Kumar, P.; Garg, P.; Solanki, K.N.; Adlakha, I.
Abstract: Hydrogen embrittlement limits the service life of various metallic components by causing a transition from a ductile to a brittle failure of inherently ductile alloys. In this work, using first-principles calculations, the effect of interstitial hydrogen on the ideal shear strength across various metals (Al, Ni, Fe, Nb, Ti, and Zr) and its implications on plasticity are discussed. The presence of hydrogen led to a volumetric expansion, which in turn had a key role in the observed shear strength response of cubic metals. However, in the case of HCP metals, the chemical contributions also have a significant part in the observed shear strength response. The interstitial hydrogen atom interacts strongly with valence d orbital metals (Ni, Fe, Nb, Ti, and Zr). Based on the Peierls-Nabarro framework, the presence of interstitial hydrogen reduces the Peierls stress across all the metals examined here. Finally, these findings provide insights to comprehensively understand hydrogen embrittlement. Graphical abstract: Image 1 Highlights: The volumetric strain by hydrogen had a key role in the shear strength response. The uninterrupted charge depletion near hydrogen led to a noticeable drop in strength. The Peierls stress was found to decrease with increasing hydrogen concentration.